2019
DOI: 10.1159/000497417
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Anopheles stephensi</i></b> Dual Oxidase Silencing Activates the Thioester-Containing Protein 1 Pathway to Suppress <b><i>Plasmodium</i></b> Development

Abstract: We characterized the dual oxidase (Duox) gene in the major Indian malaria vector Anopheles stephensi, which regulates the generation of reactive oxygen species. The AsDuox gene encodes for a 1,475-amino-acid transmembrane protein that contains an N-terminal noncytoplasmic heme peroxidase domain, a calcium-binding domain, seven transmembrane domains, and a C-terminal cytoplasmic NADPH domain. Phylogenetic analyses revealed that A. stephensi Duox protein is highly conserved and shares 97–100% amino acid identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Besides its antimicrobial activity through hydrogen peroxide production, DUOX is associated with mechanisms that reduce damage to the host's microbiota after a blood meal by lowering the intensity of the immune response (47). It has been shown that the silencing of DUOX promotes effective immune responses that include the increment of TEP1, leading to lower infection loads (48). In the particular case of A. albimanus, phenoloxidase activity (and ppo1 gene transcription) is not likely to be related to parasite death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its antimicrobial activity through hydrogen peroxide production, DUOX is associated with mechanisms that reduce damage to the host's microbiota after a blood meal by lowering the intensity of the immune response (47). It has been shown that the silencing of DUOX promotes effective immune responses that include the increment of TEP1, leading to lower infection loads (48). In the particular case of A. albimanus, phenoloxidase activity (and ppo1 gene transcription) is not likely to be related to parasite death.…”
Section: Discussionmentioning
confidence: 99%
“…Fold change transcript abundance of Brown in relation to White mosquito were as follows: lrim1 (+6.3), tep (+4.1); ctl4 (+11.6), ctl6 (+4.4), frep3 (+2.8) ( Figure 2G). In A. gambiae and A. stephensi, Dual oxidase acts as a modulator that prevents a strong immune response (47,48). Thus, the lower transcription (3.1fold) of duox in Brown mosquitoes could also contribute to its resistance condition ( Figure 2G).…”
Section: Anopheles Albimanus Phenotypes Are Different In Gdna Methylamentioning
confidence: 99%
“…For colony propagation, 4-to 5-day-old females were fed on anesthetized mice and their eggs were collected in moist conditions. The hatched larvae were floated in water to continue the life cycle and fed on a 1:1 mixture of dog food (Pet Lover's crunch milk biscuit, India) and fish food (Gold Tokyo, India) (Gupta et al, 2017;Choudhury et al, 2019;Kakani et al, 2019).…”
Section: Rearing Of Mosquitoesmentioning
confidence: 99%
“…The best matching An. stephensi contig 7145 (SuperContig KB664566 and Ensembl identifier ASTE003848) was analyzed using Augustus software to identify the full-length putative AsHPX2 gene as before (Stanke et al, 2008;Choudhury et al, 2019;Kakani et al, 2019). AsHPX2 and AgHPX2 gene sequences were aligned to design gene-specific primers.…”
Section: Retrieval Of Heme Peroxidase Ashpx2mentioning
confidence: 99%
See 1 more Smart Citation